Evaluasi Hasil Belajar Pada Siswa Di SMPN 2 Kartasura - Binti Nuraisyah; Inez Yuliane; Utari Marcela; Nurul Latifatul Inayati (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research article aims to identify what obstacles occur in the evaluation process at SMP Negeri 2 Kartasura and identify the evaluation process for PAI subject teachers at SMP Negeri 2 Kartasura on student learning outcomes. In learning, evaluation is needed to determine the learning outcomes obtained by students, where initially there were problems that caused the students not to focus during the teaching and learning process. As well as causing failure to obtain high grades. This research uses the type of literature study research. The use of this approach uses a descriptive approach which is adapted to the main objective of the research focusing on students at SMP Negeri 2 Kartasura. There are two types of data collection techniques in this research, namely interviews and documentation. These results prove that PAI teachers must also monitor students for what they experience, which causes student learning outcomes to decline